Carryover effects from embryos on larval performance in the freshwater shrimp Palaemon argentinus (Crustacea: Decapoda: Palaemonidae). Issue 1 (2nd January 2020) - Ituarte, Romina Belén; Giovagnoli, Agustina; Vázquez, María Guadalupe; Cristina Bas, Claudia
ABSTRACT: Our understanding of physiological carryover effects from embryos on post-hatching performance is still limited for aquatic organisms that brood embryos externally. We examined the effects of embryonic care experience (mother presence/absence) on larval development in the freshwater shrimp Palaemon argentinus . We compared survival rate, developmental time and number of moults …until the juvenile stage, between… larvae coming from sibling embryos isolated ( in vitro ) and attached ( in vivo ) to the female in two salinities (2, 15 PSU). Survival rates of larvae showed no changes in response to either the type of embryonic culture ( in vivo / in vitro ) or salinity treatment (average survival 62 ± 12%), although embryonic developmental rates were always faster for in vitro cultures. Low salinity lengthened larval development and larvae coming from the in vitro cultures showed the strongest responses: the juvenile was reached later with the greatest and most variable number of moults. High salinity allowed larvae to reach the juvenile stage sooner and with less moults, irrespective of the embryonic care experience. Despite the usefulness of the in vitro technique for excluding maternal influence as potentially confounding source of variation, our results warn about physiological carryover effects on post-hatching performance.